Eskatologi Dalam Padangan Hassan Hanafi dan Fazlurrahman (Studi Komparatif Epistemologi Ilmu Kalam) - Nurhidayanti, Nurhidayanti (UIN Sayyid Ali Rahmatullah Tulungagung, 2020)
Abstract The epistemology of the science of kalam of eschatology has become a part of the attention of some of the figures because it includes several branches of science. Such epistemology philosophy, The science of kalam or theology and tasawwuf. In this article, the discussion of eschatology reviewed in the science of kalam the vehicle between the two Islamic thinkers namely Hassan Hanafi and Fazlurrahman. Both offer methodology in assessing the theology which is not only limited to the concept of the formation of dogmas religious but looked at more broadly, see the social conditions as a way to re-educate, sensitize and promote the community. Among the discussion of the theology of the most important is about eschatology where the future of religion. Both figures, making the historical method in the study the concept of eschatology in Islam. The discussion of the eschatology of course discuss the world and the hereafter, but in this paper only focuses on the view between the two regarding the nature barzah, heaven, and hell. Keywords: Eskatologi, Hassan Hanafi, Fazlur rahman. Abstrak Epistemologi ilmu kalam mengenai eskatologi telah menjadi bagian perhatian beberapa tokoh karena mencakup beberapa cabang ilmu pengetahuan. Diantaranya epistemologi filsafat, ilmu kalamatau teologi dan tasawwuf. Dalam artikel ini pembahasan mengenai eskatologi ditinjau dalam ilmu kalam yang mengkomparasikan antara dua pemikir Islam yaitu Hassan Hanafi dan Fazlurrahman. Keduanya menawarkan metodologi dalam mengkaji teologi yang tidak hanya terbatas pada konsep pembentukan dogma-dogma keagamaan akan tetapi memandang lebih luas, melihat kondisi sosial sebagai jalan untuk memahamkan, menyadarkan dan memajukan masyarakat. Diantara pembahasan teologi yang terpenting adalah mengenai eskatologi diamana masa depan sebuah ajaran agama. Kedua tokoh tersebut, menjadikan metode sejarah dalam mengkaji konsep eskatologi dalam Islam. Pembahasan eskatologi tentunya membahas mengenai dunia dan akhirat, namun dalam tulisan ini hanya fokus pandangan antara keduanya mengenai alam barzah, surga dan neraka. Kata Kunci: Eskatologi, Hassan Hanafi, Fazlurrahman.